Does increased core temperature alter cognitive performance during exercise-induced heat strain? A narrative review - Doohan, M. A.; Watzek, J. T.; King, N.; White, M. J.; Stewart, I. B. (Journal of Applied Physiology, 2023)
Research to date provides equivocal evidence regarding the influence of heat stress, heat strain, and more specifically, elevated exercise-induced core temperature on cognitive performance. This review sought to identify differences in how specific cognitive tasks were affected by increases in core body temperatures. Included papers (n = 31) measured cognitive performance and core temperature during exercise, while experiencing heightened thermal stress. Cognitive tasks were classified as cognitive inhibition, working memory, or cognitive flexibility tasks. Independently, core temperature changes were not sufficient predictors of cognitive performance. However, reaction time, memory recall, and Stroop tasks appeared to be most effective at identifying cognitive changes during heightened thermal strain. Alterations in performance were more likely to arise under increased thermal loads, which were typically associated with cumulative physiological stressors, such as elevated core temperatures, occurring alongside dehydration, and prolonged exercise durations. Future experimental designs should consider the relevance, or futility of assessing cognitive performance in activities that do not elicit a considerable degree of heat strain, or physiological load.